2015
DOI: 10.32677/ijch.2015.v02.i04.018
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profiles and risk factors for neonatal sepsis in a rural tertiary care hospital in north India

Abstract: Objectives: To study, the bacterial profile in cases of neonatal sepsis admitted to the neonatal nursery or neonatal intensive care unit (NICU) and to identify the risk factors for early-onset neonatal sepsis. Design: Retrospective survey of hospital records from January 2012 to December 2012. Setting: A neonatal unit of a rural medical college hospital. Subjects: All inborn and outborn neonates who either had clinical signs of sepsis or were born to mothers with risk factors for sepsis and underwent a sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Also, contamination from mothers and caregivers may have led to an increase in the rate of transmission of Staphylococcus aureus in these neonates. However, studies conducted in India 7 and Pakistan, 28 found the presence of Gram-negative bacterial organisms to be more than Gram-positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, contamination from mothers and caregivers may have led to an increase in the rate of transmission of Staphylococcus aureus in these neonates. However, studies conducted in India 7 and Pakistan, 28 found the presence of Gram-negative bacterial organisms to be more than Gram-positive.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 The spectrum of causative organisms responsible for neonatal infection varies across different geographical areas and changes over time, even in the same place. 7 Group B Streptococcus was found to be the most prevalent organism causing NNS in a study conducted in England, 8 while in India, 9 it was observed that Klebsiella pneumoniae was the most prevalent organism isolated. From a study in Ethiopia, 2 Staphylococcus aureus was observed to be the most prevalent organism isolated.…”
Section: Introductionmentioning
confidence: 97%